Motivating Physicians to Report Adverse Medical Events in China: Stick or Carrot?. Issue 5 (August 2021) - Xue, Yajiong; Yang, Jing; Zhang, Jing; Luo, Mengyun; Zhang, Zhiruo; Liang, Huigang
Abstract : Background: Adverse medical events (AMEs) pose serious threats to patient safety. One of the major challenges of AME reporting is low physician engagement. This study attempted to examine how punishment and reward can improve physicians' AME reporting in China. Methods: A survey was conducted in a large hospital with 1693 beds in China. Data were collected from 311 physicians. Ordinal and binary logistic regression was used for data analysis. Results: This study reveals that both punishment and reward are positively associated with intention to report AMEs. There is a negative interaction effect between punishment and reward. Although collective punishment is positively associated with intention to report AMEs, collective reward is not. Moreover, the physicians who have fear of negative consequences of AMEs and lack knowledge of AME reporting have lower intention to report AMEs. These findings do not differ between male and female physicians. Conclusions: This survey suggests that punishment and reward have potential to motivate Chinese physicians to report AMEs. However, the implementation strategies of these control mechanisms may not be universally applicable and should be carefully designed on the basis of the specific characteristics of the practice site.